2014
DOI: 10.1080/14330237.2014.980629
|View full text |Cite
|
Sign up to set email alerts
|

A critical engagement with the DSM-5 and psychiatric diagnosis

Abstract: Abstract:Classifications in psychiatry can result in the reification of hypothetical approaches, arbitrary categorization and social injustice. This article applies a social constructivist approach to critique the DSM-5 as a neurobiological model of psychiatric diagnosis which ignores psychosocial factors such as poverty, unemployment and trauma as causes of mental distress. It challenges the universality of psychiatric diagnosis and proposes that cultural psychiatry"s framing of "culture-bound syndromes," or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
5
0
2
Order By: Relevance
“…Thus, not only is the DSM positioned as a formal source of classifying sexual problems but it is also given a formidable, religious-like, measure of authority. Furthermore, the DSM, like the Bible, is largely based on a Western perspective, allotting it a certain amount of privilege over non-Westernized models of health, illness and normalcy in North America (Kriegler and Bester, 2014). By connecting the DSM to the Bible, the textbook strengthens the ‘inherent’ power of the medical approach and, in turn, marginalizes more holistic approaches to health and illness that exist in many non-Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, not only is the DSM positioned as a formal source of classifying sexual problems but it is also given a formidable, religious-like, measure of authority. Furthermore, the DSM, like the Bible, is largely based on a Western perspective, allotting it a certain amount of privilege over non-Westernized models of health, illness and normalcy in North America (Kriegler and Bester, 2014). By connecting the DSM to the Bible, the textbook strengthens the ‘inherent’ power of the medical approach and, in turn, marginalizes more holistic approaches to health and illness that exist in many non-Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…April, 2022 Angermeyer & Matschinger (2005) states that classifications in psychiatry can become inhuman labeling systems or potential sources for social and political violence. Intense protests for DSM-V are connected to transparency problems, field trials, links with pharmaceutical industry and mostly the intense focus to the biomedical definition of a mental disorder (Kriegler & Bester, 2014). Various studies using the DSM as a diagnostic tool have been shown to address validity issues and while seemingly reliable, various problems are usually identified in the research sequence (Barber, 2014).…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
“…Since friendly visiting and the settlement house era, the field of Social Work has not made much progress towards decolonization (Gray et al, 2013). Examples in practice include the biopsychosocial assessment which is rooted in white values and belief systems around problem formation, strengths, and treatment planning (Almeida et al, 2019;McNay, 1992) as well as using the DSM-V as a diagnostic tool that is based on a Western medical model which pathologizes client responses to individual, collective, and systemic traumas (Jacob et al, 2013;Kriegler & Bester, 2014); Also, in social work education courses labeled as "diversity" or "cultural competence", in which whiteness is held to the standard from which "others" deviate and become "otherized," are numerous. Almeida and colleagues (2019) make a critical point in stating "...terms like multiculturalism, intolerance, diversity, cultural competence, cultural humility, and cultural sensitivity all emerged without an interrogation of cultural imperialism and coloniality" (p. 159), that further perpetuates oppressive structures throughout the profession.…”
Section: White Supremacy and Social Workmentioning
confidence: 99%